Competing with New Product Technologies: A Process Model of Strategy - Das, Shobha S.; Van de Ven, Andrew H. (Management Science, 2000)
This paper draws upon research in the economics of technical change and in the social construction of technology to develop and test a process model of strategy. We conducted a longitudinal study of leading firms that were sponsoring new and competing product technologies in two industries: the videoplayer industry and the medical diagnostic imaging industry. We built original datasets on the actions of these firms, and then empirically examined the strategy process. Our findings indicate that the nature of the product technology, whether novel or evolved, and the market, whether concentrated or dispersed, influences when firms use technical or institutional strategies to get their new product technology accepted by the market.